Karakteristik Kekerasan Coran Material Al-7Si Akibat Variasi Temperatur Tuang Dan Tebal Saluran Pada Pengecoran Sand Casting - Putra, Putu Andika Pramana; Sugita, I Ketut Gede; Dwidiani, Ni Made (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstractt The Al-Si alloy is a vital aluminum-based alloy due to its excellent casting characteristics, good weldability, high pressure tightness, and corrosion resistance. Al-7Si alloy is frequently used in the maritime, electrical, automotive, and aerospace industries, especially for components such as engine blocks and cylinder heads as well as other machine body castings. The pouring temperature plays a crucial role in ensuring that the material fills the mold perfectly and prevents defects such as porosity or gas bubbles. The thickness of the channel also affects the filling speed of the mold and the cooling process of the liquid material. Optimal regulation of these two parameters can influence the mechanical properties of the cast material. Therefore, the aim of this study is to investigate the effect of casting temperature variation and channel thickness variation on the hardness of Al-7Si material. This research involves the use of varying casting temperatures between 750°C, 850°C, and 950°C, as well as channel thickness variations from 1.5 mm to 5 mm. The results show that the highest hardness occurs at a casting temperature of 750°C, while the lowest hardness occurs at a casting temperature of 950°C. Keywords: Al-7Si, pouring temperature, channel thickness, hardness.